Pattern and Outcomes of Respiratory Diseases in Geriatric Patients at a Tertiary Care Hospital in Bangladesh (Bangladesh Medical Journal, 2026)
Respiratory diseases are a major cause of morbidity and mortality among geriatric populations, particularly in developing countries like Bangladesh. Age-related physiological decline, cumulative environmental exposures, and coexisting comorbidities increase susceptibility to respiratory illnesses in the elderly. However, hospital-based data describing the patterns and outcomes of these conditions remain limited. This study aimed to assess the pattern of respiratory problems, clinical presentation, and outcomes among geriatric patients admitted to Dhaka Medical College Hospital (DMCH), and to evaluate disease severity using the Medical Research Council (MRC) breathlessness scale. This cross-sectional observational study was conducted in the indoor medicine wards of DMCH from January 2016 to July 2016. A total of 100 geriatric patients (aged ≥60 years) with respiratory complaints were selected purposively. Data were collected using a structured questionnaire, clinical examination, and relevant investigations. Variables included age distribution, presenting symptoms, diagnoses, and outcomes. Dyspnea severity was assessed among 72 patients using the MRC scale. Data were analyzed using descriptive statistics and presented as frequencies and percentages. The mean (±SD) age of the study population was 72.87 ± 6.69 years, with the majority belonging to the 66–70 years age group (47%). The most common presenting symptom was cough (100%), followed by fever (82%), breathlessness (72%), chest pain (46%), weight loss (44%), and haemoptysis (36%), while voice change (4%) was the least common. Regarding disease pattern, pneumonia (35%) was the most frequent diagnosis, followed by chronic obstructive pulmonary disease (COPD) (25%), pulmonary tuberculosis (14%), bronchial asthma (8%), and bronchial carcinoma (7%). Less common conditions included bronchiectasis (4%), lung abscess (4%), aspiration pneumonia (2%), and diffuse parenchymal lung disease (1%). Outcome analysis revealed varying fatality rates across conditions. The highest mortality was observed in aspiration pneumonia (100%), followed by acute severe bronchial asthma (50%), bronchial carcinoma (42.86%), pneumonia (28.57%), acute exacerbation of COPD (20%), and pulmonary tuberculosis (14.28%). These findings indicate significant disease burden and variable prognosis among different respiratory conditions. Respiratory diseases, particularly pneumonia and COPD, are highly prevalent among geriatric patients admitted to tertiary care hospitals. The high frequency of severe presentations and notable mortality rates underscores the need for early diagnosis, prompt management, and preventive strategies. Strengthening geriatric-focused respiratory care services is essential to reduce morbidity and mortality in this vulnerable population.Bangladesh Med J. 2025 May; 54(2): 13-20